1994
DOI: 10.1148/radiology.193.2.7972758
|View full text |Cite
|
Sign up to set email alerts
|

Posterosuperior glenoid impingement of the shoulder: findings at MR imaging and MR arthrography with arthroscopic correlation.

Abstract: Impingement of the rotator cuff on the posterior superior glenoid labrum is a cause of posterior shoulder pain in athletes who throw. MR arthrography may allow detection of abnormalities associated with this clinical entity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
2

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(39 citation statements)
references
References 0 publications
0
37
0
2
Order By: Relevance
“…Queste due indagini sono effettivamente superiori alle corrispondenti valutazioni TC o RM dirette, ovvero eseguite senza somministrazione di mezzo di contrasto (MdC), grazie alla risoluzione di contrasto e alla distensione della capsula articolare ottenute mediante somministrazione intraarticolare di MdC paramagnetico o iodato opportunamente diluiti in soluzione fisiologica [1][2][3][4][5][6]. La valutazione della sede, del tipo e dell'estensione delle alterazioni è più attendibile, in particolare in presenza di lesioni della cuffia dei rotatori [2,7,8] e dell'instabilità gleno-omerale congenita o traumatica [9][10][11]. Le due indagini forniscono un'informazione non sovrapponibile in virtù della più alta sensibilità della TC per le calcificazioni e le alterazioni ossee [11,12] e dell'ottimale risoluzione di contrasto della RM per le lesioni dei tessuti molli [2,3,7,11,13].…”
Section: Methodsunclassified
See 1 more Smart Citation
“…Queste due indagini sono effettivamente superiori alle corrispondenti valutazioni TC o RM dirette, ovvero eseguite senza somministrazione di mezzo di contrasto (MdC), grazie alla risoluzione di contrasto e alla distensione della capsula articolare ottenute mediante somministrazione intraarticolare di MdC paramagnetico o iodato opportunamente diluiti in soluzione fisiologica [1][2][3][4][5][6]. La valutazione della sede, del tipo e dell'estensione delle alterazioni è più attendibile, in particolare in presenza di lesioni della cuffia dei rotatori [2,7,8] e dell'instabilità gleno-omerale congenita o traumatica [9][10][11]. Le due indagini forniscono un'informazione non sovrapponibile in virtù della più alta sensibilità della TC per le calcificazioni e le alterazioni ossee [11,12] e dell'ottimale risoluzione di contrasto della RM per le lesioni dei tessuti molli [2,3,7,11,13].…”
Section: Methodsunclassified
“…These two imaging procedures are definitely better than plain CT or MRI of the shoulder because of the contrast resolution due to the presence of intra-articular diluted paramagnetic contrast or iodinated agent, respectively, and to the distension of the of the joint capsule [1][2][3][4][5][6]. The evaluation of site, type, grade, and extent of the disease is more reliable, in particular for rotator cuff tears [2,7,8] and congenital or traumatic glenohumeral instability [9][10][11]. The two techniques give different information due to a higher CT sensitivity for calcifications and bone injuries [11,12] and an optimal MR contrast resolution for soft tissue abnormalities [2,3,7,11,13].…”
Section: Introductionmentioning
confidence: 99%
“…In 1994, Tirman et al 11,12 reported MRI in ABER and indicated that this procedure was useful for clarifying the status of patients with rupture of the rotator cuff, posterosuperior impingement, and recurrent instability. 13 Neumann et al 8 pointed out that the AIGHL was well detected on MR images in ABER.…”
Section: Discussionmentioning
confidence: 99%
“…Dans l'épaule du sportif, les lésions sont variées [47][48][49][50][51][52][53][54][55]. Elles peuvent être intra-ou extra-articulaires et sont en général de petite taille.…”
Section: éPaule Du Sportifunclassified